Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1200/jco.2005.04.7779
|View full text |Cite
|
Sign up to set email alerts
|

Frequency, Characteristics, and Reversibility of Peripheral Neuropathy During Treatment of Advanced Multiple Myeloma With Bortezomib

Abstract: Bortezomib-associated peripheral neuropathy seemed reversible in the majority of patients after dose reduction or discontinuation. Although severe neuropathy was more frequent in the presence of baseline neuropathy, the overall occurrence was independent of baseline neuropathy or type of prior therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

28
476
5
10

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 591 publications
(519 citation statements)
references
References 18 publications
28
476
5
10
Order By: Relevance
“…In particular, the short duration of therapy may minimize cumulative peripheral neuropathy arising from treatment. Both bortezomib 42,43 and thalidomide [44][45][46] are associated with peripheral neuropathy, so a possible increase in the incidence of peripheral neuropathy when these agents are combined was a concern with BTD therapy. However, the 45% rate of neuropathy reported in our analysis appears similar to that reported with bortezomib plus melphalan and prednisone in previously untreated patients in the VISTA phase 3 study (44%) 4 and with single-agent bortezomib in the Assessment of Proteasome Inhibition on Extending Remissions (APEX) phase 3 study (37%) 43 ; the 9% rate of grade 3 events also appears similar to the rates reported in VISTA (13%) 4 and APEX (9%), 43 in the GIMEMA phase 3 study of BTD (9%), 13 in the IFM phase 3 study of bortezomib plus dexamethasone (7%), 38 and in phase 3 studies of thalidomide plus dexamethasone (3%-7%).…”
Section: Original Article 3148mentioning
confidence: 99%
“…In particular, the short duration of therapy may minimize cumulative peripheral neuropathy arising from treatment. Both bortezomib 42,43 and thalidomide [44][45][46] are associated with peripheral neuropathy, so a possible increase in the incidence of peripheral neuropathy when these agents are combined was a concern with BTD therapy. However, the 45% rate of neuropathy reported in our analysis appears similar to that reported with bortezomib plus melphalan and prednisone in previously untreated patients in the VISTA phase 3 study (44%) 4 and with single-agent bortezomib in the Assessment of Proteasome Inhibition on Extending Remissions (APEX) phase 3 study (37%) 43 ; the 9% rate of grade 3 events also appears similar to the rates reported in VISTA (13%) 4 and APEX (9%), 43 in the GIMEMA phase 3 study of BTD (9%), 13 in the IFM phase 3 study of bortezomib plus dexamethasone (7%), 38 and in phase 3 studies of thalidomide plus dexamethasone (3%-7%).…”
Section: Original Article 3148mentioning
confidence: 99%
“…Three proteasome inhibitors (PIs), bortezomib (BTZ: Kane et al , 2003; Richardson et al , 2003, 2005), carfilzomib (CFZ) and ixazomib (IXZ) are currently approved for the treatment of MM, with several others in development. Although important therapeutic advances, these PIs are associated with significant and dose‐limiting off‐target toxicities (Lonial et al , 2005; Richardson et al , 2006; Cai et al , 2014; Harvey, 2014; Atrash et al , 2015; Wanchoo et al , 2015) and the development of acquired resistance (Fall et al , 2014; Huber et al , 2015; Niewerth et al , 2015). Despite consistently high response rates with PI‐based combinations, almost all MM patients eventually relapse, with progressively lower rates and durations of response with each subsequent line of therapy and poor prognosis as resistance emerges (Kumar et al , 2012).…”
mentioning
confidence: 99%
“…3) [23], the most common adverse events for all patients with MM at the standard 1.3-mg/m 2 dose of bortezomib were asthenia (fatigue, weakness, malaise) (65%), gastrointestinal effects (nausea, 64%; diarrhea, 51%; constipation, 43%; vomiting, 36%), thrombocytopenia (43%), and PN (37%), with the latter usually being reversible [24].…”
Section: Management Of Side Effects During Bortezomib Therapymentioning
confidence: 99%